Knowledge, attitude and practice on smoking cessation guideline among medical doctors attending Family Medicine Scientific Conference 2016 - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki Bin Mohamed; Mohd Rus, Razman; Jamani, Nurjasmine Aida (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Prevalence of active smokers in Malaysia remains high despite the availability of stop-smoking services. Rather than focusing on patients’demotivating factors, possible poor performance from providers should be evaluated. Thus, knowledge, attitude and practice of the healthcare professional on smoking cessation intervention needs to be assessed, especially among primary care doctors.